Adapting and piloting a cognitive-behavioural group therapy-based anxiety intervention programme for vulnerable children from a disadvantaged background within the South African context - Myburgh, Naomi (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.